Molecular Epidemiology of Enterococcal Bacteremia in Australia - Coombs, Geoffrey; Pearson, Julie; Daley, D.; Le, T.; Robinson, James; Gottlieb, T.; Howden, B.; Johnson, P.; Bennett, C.; Stinear, T.; Turnidge, J. (American Society for Microbiology, 2014)
Enterococci are a major cause of health care-associated infections and account for approximately 10% of all bacteremias globally. The aim of this study was to determine the proportion of enterococcal bacteremia isolates in Australia that are antimicrobial resistant, with particular emphasis on susceptibility to ampicillin and the glycopeptides, and to characterize the molecular epidemiology of the Enterococcus faecalis and Enterococcus faecium isolates. From 1 January to 31 December 2011, 1,079 unique episodes of bacteremia were investigated, of which 95.8% were caused by either E. faecalis (61.0%) or E. faecium (34.8%). The majority of bacteremias were health care associated, and approximately one-third were polymicrobial. Ampicillin resistance was detected in 90.4% of E. faecium isolates but was not detected in E. faecalis isolates. Vancomycin nonsusceptibility was reported in 0.6% and 36.5% of E. faecalis and E. faecium isolates, respectively. Unlike Europe and the United States, where vancomycin resistance in E. faecium is predominately due to the acquisition of the vanA operon, 98.4% of E. faecium isolates harboring van genes carried the vanB operon, and 16.1% of the vanB E. faecium isolates had vancomycin MICs at or below the susceptible breakpoint of the CLSI. Although molecular typing identified 126 E. faecalis pulsed-field gel electrophoresis pulsotypes, >50% belonged to two pulsotypes that were isolated across Australia. E. faecium consisted of 73 pulsotypes from which 43 multilocus sequence types were identified. Almost 90% of the E. faecium isolates were identified as CC17 clones, of which approximately half were characterized as ST203, which was isolated Australia-wide. In conclusion, the Australian Enterococcal Sepsis Outcome Programme (AESOP) study has shown that although they are polyclonal, enterococcal bacteremias in Australia are frequently caused by ampicillin-resistant vanB E. faecium.